Empati Dan Penulisan Dokumen: Suatu Analisis Kesantunan Berbahasa - Melor Fauzita Md. Yusoff, Dr; Nor Hafidah Ibrahim; Rohaya Md Ali; Nor Hasimah Ismail (International Consortium of Education and Culture Research Studies, 2017)
Empathy is derived from Greek. Empathy can be generally defined as the ability of a person to know and feel the feelings of others. The ability of someone in delving into the feelings of others is capable of strengthening the relationship between the person with someone else. Empathy is seen as the way a person understands something problems experienced by others and strives to show that he's hard to understand the feelings of the person. Early Islam language is clear that picture liver beam represented through the behavior and use of language politeness that do not offend either to read or listen. As such, this paper will examine the practice of writing early speaking class of managers through management documents issued to the public based on a sense of empathy are shown. The review approach is to use analytical methods of document management documents obtained from selected government departments. Early writing speaking will be classified based on four key principles, namely, the most delicate, subtle, less fine and gross. The result saw the class Manager highly on related matters expressed impati. This is evident when there is a use of words in the form of empathy that is used in accordance with the context of the document was issued.